2015
DOI: 10.3311/ppci.7364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warm Mix Asphalt Additives on Aging Characteristics of Bituminous Mixtures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The reported results showed that significant changes occur in properties of produced WMA samples and the level of changes are depended on bitumen and additive type as well as additive rates. Dokandari and Topal [38] investigated the short and long-term aged properties of WMA produced with foamed and nonfoamed additive up to 7% by weight of bitumen in rate. Conventional bitumen tests and the indirect tension tests were performed on WMA samples.…”
Section: Article Info Abstractmentioning
confidence: 99%
“…The reported results showed that significant changes occur in properties of produced WMA samples and the level of changes are depended on bitumen and additive type as well as additive rates. Dokandari and Topal [38] investigated the short and long-term aged properties of WMA produced with foamed and nonfoamed additive up to 7% by weight of bitumen in rate. Conventional bitumen tests and the indirect tension tests were performed on WMA samples.…”
Section: Article Info Abstractmentioning
confidence: 99%
“…Mixture with temperatures which is lower than minimum would be impossible to compact because of viscosity. For mixing and compaction temperatures optimal content of zeolite is 5% relative to ashalt binder [14,15,16,21]. With this percentage content minimal temperature range is obtained.…”
Section: Effect Of Zeolite On the Performance Of Asphalt Mixturesmentioning
confidence: 99%
“…Table 1 shows the change of link performance of bitumen, depending on the amount and type of zeolite [14]. With increasing the content of zeolite, penetration value decreases [14,15,16,17]. The softening point is determined as the temperature at which a sample of bitumen, subjected to a progressive increase of temperature and the weight of a steel sphere, reaches a consistence that leads to its flow through a ring of steel, until obtain a specific deformation.…”
Section: Figure 4-model Of Clinoptilolite Structure [9]mentioning
confidence: 99%
See 1 more Smart Citation
“…ese reductions in mixing and compaction temperatures greatly reduce asphalt smoke emissions and energy consumption and can greatly reduce the aging of the asphalt binder, thus increasing the service life of asphalt pavement [7,8]. As the compaction performance of low-temperature asphalt improves, asphalt's limited transportation and construction times can be extended [9].…”
Section: Introductionmentioning
confidence: 99%